Well-posedness and nonsmooth Lyapunov pairs for state-dependent maximal monotone differential inclusions. (2nd June 2020) - Le, Ba Khiet
ABSTRACT: In this paper, we introduce a class of state-dependent maximal monotone differential inclusions. The existence and uniqueness of solutions are obtained by using an implicit discretization scheme and a kind of hypo-monotonicity assumption. In addition, a characterization for nonsmooth Lyapunov pairs associated with such systems is provided. Our result can be applied to study state-dependent sweeping processes and Lur'e dynamical systems. It is new even the involved maximal monotone operators depend only on the time.